FEATURES OF FORMATION AND DEVELOPMENT OF THE INVESTIGATIVE ACTIONS CONNECTED WITH QUESTIONING (Journal of actual problems of jurisprudence, 2019)
Article is devoted to questions of a ratio of the criminal proceedings, criminalistics and operational search activity which influenced formation and development of the investigative actions connected with questioning. Formation of procedural provisions of inquiry and tactics of its carrying out is impossible without interaction, interdependence and interpenetration of criminal proceedings, criminalistics and operational search activity. As practice shows, the use of the results, received during the operational search activity, in proof on criminal cases promotes the effectiveness of inquiry. Article analyses existing and modern criminal procedure legislation, that formulatesproposals for improvement of the national legislation. On the basis of the conducted research authors come to a conclusion that the criminalistics quite often is in the lead in research and development, which then are transformed to the legal procedure and to science of criminal procedure law. The history of the domestic criminal procedure legislation and criminalistics brightly highlights this picture. As a result of interaction, interdependence and interpenetration of criminal proceedings and criminalistics procedural emergence of such investigative actions connected with obtaining evidences as face-to-face interrogation, presentation for identification, check and specification of indications on the place, an investigative experiment, deposition of evidences became possible. And these investigative actions “detached” from interrogation. In too time in spite of the fact that the specified investigative actions are independent, their production is possible only after interrogation. Besides, for increase in guarantees of legality, ensuring protection of the rights and the interests of the persons who are involved in criminal proceedings and also the effectiveness of investigation it is necessary to regulate the provisions reflecting the procedure of receiving explanations in the Code of Criminal Procedure of the Republic of Kazakhstan. Laws of the Republic of Kazakhstan, the Criminal Code of RK, the Code of Criminal Procedure of RK and works of the known scientific protsessualist and criminalists of Kazakhstan and foreign countries makes scientific and methodological basis.